2023
DOI: 10.1111/eci.13969
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after transvenous lead extraction: A risk prediction model for sustainable care delivery

Abstract: Background and Aims:Transvenous lead extraction (TLE) has become a pivotal part of a comprehensive lead management strategy, dealing with a continuously increasing demand. Nonetheless, the literature about the long-term impact of TLE on survivals is still lacking. Given these knowledge gaps, the aim of our study was to analyse very long-term mortality in patients undergoing TLE in public health perspective. Methods:This prospective, single-centre, observational study enrolled consecutive patients with cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“… 1 On the other hand, elderly patients have been reported to be 1 of the predictors of higher long-term mortality rates in patients undergoing TLE. 2 Additionally, the ELECTRa (The European Lead Extraction ConTRolled) registry has associated a previously abandoned lead at the time of TLE with increased procedural failure and major complications. 3 Hussein et al 4 have also reported that TLE in patients with abandoned leads was more likely to require specialized extraction tools and an adjunctive rescue femoral approach.…”
Section: Discussionmentioning
confidence: 99%
“… 1 On the other hand, elderly patients have been reported to be 1 of the predictors of higher long-term mortality rates in patients undergoing TLE. 2 Additionally, the ELECTRa (The European Lead Extraction ConTRolled) registry has associated a previously abandoned lead at the time of TLE with increased procedural failure and major complications. 3 Hussein et al 4 have also reported that TLE in patients with abandoned leads was more likely to require specialized extraction tools and an adjunctive rescue femoral approach.…”
Section: Discussionmentioning
confidence: 99%